Clinical features of neonatal hyperthyroidism: a retrospective analysis in southwestern China - Song, Yan; Wei, Hong; Cao, Luying; Deng, Pinglan; Du, Weixia; Liu, Shan; Zhang, Yu (Frontiers in Pediatrics, 2024)
Purpose To explore the clinical characteristics and to evaluate different types of thyroid dysfunction in babies with neonatal hyperthyroidism(NH). Methods The clinical data of 19 neonates with hyperthyroidism admitted to Children ’s Hospital of Chongqing Medical University from January 2012 to April 2021were retrospectively analyzed. Results Fifteen (78.9%) infants were born to mothers with Graves ’ disease (GD).Eleven(57.9％) of the infants were premature; two babies were born as SGA. The age at diagnosis ranged from 3 to 34 d, with a mean of (18.53±6.85) d. Majority of the babies presented goiter(84.2％）and tachycardia(94.7％）after birth. Nine(47.4％) of them presented with abnormal weight gain, seven(36.8 ％ ）with stare or ocular protrusion, six（31.6％）with hyperexcitability, four(21. 1％） with jaundice and liver dysfunction, two(10.5％） with sweating, one（5.3％） with fever, and one case without any symptoms.Transient hyperthyroidism was the main thyroid dysfunction in our study. Overt hyperthyroidism was diagnosed in 13 (68.4%) neonates. Another 3 (15.8%) babies presented hyperthyroidism with slightly elevated fT3 levels ，normal T4 levels and low TSH levels. Normal thyroid hormone levels with low TSH levels were observed in 3(15.8％) neonates. Ten children were treated with anti-thyroid drugs. Eighteen children recovered normal thyroid function at 1 to 3 months of age, one baby in the study group required further levothyroxine (L-T4) supplementation due to primary hypothyroidism. One child was found to have developmental delay at 2 years of age during follow-up. Conclusions Our study highlights the need for prolonged monitoring of thyroid function in suspected patients, a single normal screening or no maternal history of hyperthyroidism can not exclude this disease.